Cancer survival stories: Perception, creation, and potential use case - Claudia Canella; Martin Inderbitzin; Manuela Oehler; Claudia M. Witt; Jürgen Barth (Health Expectations, 2023)
Abstract Background Cancer patients often search for information about their health conditions online. Cancer patient narratives have established themselves as a way of providing information and education but also as an effective approach to improving coping with the disease. Objective We investigated how people affected by cancer perceive cancer patient narratives and whether such stories can potentially improve coping during their own cancer journeys. Additionally, we reflected on whether our co‐creative citizen science approach can contribute to gaining knowledge about cancer survival stories and providing peer support. Design, Setting and Stakeholders We applied a co‐creative citizen science approach by using quantitative and qualitative research methods with stakeholders (i.e., cancer patients, their relatives, friends and health professionals). Main Outcome Measures Understandability and perceived benefits of cancer survival stories, coping, emotional reactions to the stories and helpful characteristics of the stories. Results Cancer survival stories were considered intelligible and beneficial, and they potentially support positive emotions and coping in people affected by cancer. Together with the stakeholders, we identified four main characteristics that evoked positive emotions and that were considered especially helpful: (1) positive attitudes towards life, (2) encouraging cancer journeys, (3) individual coping strategies for everyday challenges and (4) openly shared vulnerabilities. Conclusions Cancer survival stories potentially support positive emotions and coping in people affected by cancer. A citizen science approach is suitable for identifying relevant characteristics of cancer survival stories and may become a helpful educational peer support resource for people coping with cancer. Patient or Public Contributions We adopted a co‐creative citizen science approach, wherein citizens and researchers were equally involved throughout the entire project.